2018
DOI: 10.1097/brs.0000000000002712
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent Disc Degeneration After Lumbar Total Disc Replacement or Nonoperative Treatment

Abstract: 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…4, [15][16][17][18][19][20][21][22] A recent study showed no significant difference in adjacent segment degeneration rates at 8 years between patients who underwent lumbar TDR (42%) and those who continued with nonsurgical treatment (40%). 23 These data suggest that the progression of adjacent segment degeneration is part of the natural history of DDD but may be accelerated by lumbar fusion. Consistent with clinical evidence, biomechanical data demonstrate that the loss of motion caused by spinal fusion transfers stresses to adjacent spinal regions and causes accelerated degeneration.…”
Section: Introductionmentioning
confidence: 86%
“…4, [15][16][17][18][19][20][21][22] A recent study showed no significant difference in adjacent segment degeneration rates at 8 years between patients who underwent lumbar TDR (42%) and those who continued with nonsurgical treatment (40%). 23 These data suggest that the progression of adjacent segment degeneration is part of the natural history of DDD but may be accelerated by lumbar fusion. Consistent with clinical evidence, biomechanical data demonstrate that the loss of motion caused by spinal fusion transfers stresses to adjacent spinal regions and causes accelerated degeneration.…”
Section: Introductionmentioning
confidence: 86%
“…A meta-analysis 13 that evaluated surgery with simple discectomy and discectomy with bone-anchored device versus continued conservative treatment, presented evidence that surgery is more effective for symptom relief than persisting with continued conservative treatment in cases where the patient is refractory to initial conservative treatment 13 . The evaluation of the success or failure of disc protrusion treatment by the quantitative sensory test (QST), which uses different stimuli to evaluate the perception of temperature and pain, found no differences in all parameters evaluated at the 3 to6 months follow-ups in patients treated conservatively with steroid injections or with surgical treatment 14 . One of the studies compared total disc replacement surgery in 69 patients.…”
Section: Resultsmentioning
confidence: 99%
“…NSAIDs = nonsteroidal anti-inflammatory drugs. The studies 5,[6][7][8][9]11,13,14,17,20 report that conservative management is most beneficial to patients, while studies 10,11,12,15 report that surgical management is most beneficial to patients.…”
Section: Not Specifiedmentioning
confidence: 99%
“…The randomized controlled trial of Furunes et al . 52 demonstrated that there was no significant difference in the increase in the rate of adjacent segment degeneration after TDA compared with the non‐operative group, indicating that TDA does not increase the risk of adjacent segment degeneration. Berg et al .…”
Section: Surgical Treatmentmentioning
confidence: 90%
“…Although both operations had satisfactory results for pain relief, TDA showed a better trend at 5-year follow-up. The randomized controlled trial of Furunes et al 52 demonstrated that there was no significant difference in the increase in the rate of adjacent segment degeneration after TDA compared with the non-operative group, indicating that TDA does not increase the risk of adjacent segment degeneration. Berg et al 53 used distortion-compensated Roentgen analysis to evaluate the difference between TDA and intervertebral disc fusion.…”
Section: Total Disc Replacementmentioning
confidence: 99%